«Too much ideological bitterness has been added to this issue»: V. N. Andreev’s correspondence with M. Finley - Karpyuk, Sergey G. (Journal of the Belarusian State University. History, 2022)
The documents of M. Finley in the library of Cambridge University and in the personal fund of V. N. Andreev in the manuscript department of the Russian National Library in Saint Petersburg contain letters from two historians. The correspondence of M. Finley and V. N. Andreev shows that the Soviet scientist was not only a situational Finlean, but also quite consciously followed the principles of M. Finley’s work with sources. Acquaintance with M. Finley’s works and correspondence with him significantly influenced V. N. Andreev: he became a follower of an English scientist, working outside the framework of scientific schools that existed in Soviet scholarship. Correspondence with M. Finley shows a high degree of inclusion of a Soviet scientist in the current agenda of world science about Antiquity in the late 1950s – first half of the 1960s, however, the closeness of the Soviet scientific community, the lack of full-fledged international communication did not contribute to the perception of V. N. Andreev’s ideas by Western scientists. For M. Finley, V. N. Andreev was apparently just one of his many followers scattered around the world. The lack of personal contact did not allow this position to be changed. The very fact that the Soviet scientist in matters of methodology followed and listened to the advice of the scientist of the «bourgeois» testified that the Soviet historiography of Antiquity since the late 1950s could no longer be perceived as a single stream; the Soviet historical narrative of the thaw era ceases to be unified.